Is overwork weakness relevant in Charcot–Marie–Tooth disease?. Issue 12 (21st March 2014) - Piscosquito, G; Reilly, M M; Schenone, A; Fabrizi, G M; Cavallaro, T; Santoro, L; Vita, G; Quattrone, A; Padua, L; Gemignani, F; Visioli, F; Laurà, M; et al.
Abstract : Background: In overwork weakness (OW), muscles are increasingly weakened by exercise, work or daily activities. Although it is a well-established phenomenon in several neuromuscular disorders, it is debated whether it occurs in Charcot–Marie–Tooth disease (CMT). Dominant limb muscles undergo a heavier overload than non-dominant and therefore if OW occurs we would expect them to become weaker. Four previous studies, comparing dominant and non-dominant hand strength in CMT series employing manual testing or myometry, gave contradictory results. Moreover, none of them examined the behaviour of lower limb muscles. Methods: We tested the OW hypothesis in 271 CMT1A adult patients by comparing bilateral intrinsic hand and leg muscle strength with manual testing as well as manual dexterity. Results: We found no significant difference between sides for the strength of first dorsal interosseous, abductor pollicis brevis, anterior tibialis and triceps surae. Dominant side muscles did not become weaker than non-dominant with increasing age and disease severity (assessed with the CMT Neuropathy Score); in fact, the dominant triceps surae was slightly stronger than the non-dominant with increasing age and disease severity. Discussion: Our data does not support the OW hypothesis and the consequent harmful effect of exercise in patients with CMT1A. Physical activity should be encouraged, and rehabilitation remains the most effective treatment for CMT patients.